Progress in integrated and fiber optics for time-bin based quantum information processing - Montaut, Nicola; George, Agnes; Monika, Monika; Nosrati, Farzam; Yu, Hao; Sciara, Stefania; Crockett, Benjamin; Peschel, Ulf; Wang, Zhiming; Lo Franco, Rosario; Chemnitz, Mario; Munro, William J.; et al. (Advanced Optical Technologies, 2025)
The development of integrated photonic systems, both on-chip and fiber-based, has transformed quantum photonics by replacing bulky, fragile free-space optical setups with compact, efficient, and robust circuits. Photonic platforms incorporating fiber-connected sources of correlated and entangled photon pairs offer practical advantages, such as operation at room temperature, efficient integration with telecom infrastructure, and compatibility with mature and efficient semiconductor fabrication processes for cost-effective and large-scale optical circuits. The stability and scalability of integrated quantum photonics platforms have facilitated the generation and processing of quantum information in the temporal domain within a single spatial mode. Time-bin encoded states, known for their robustness against decoherence and compatibility with existing fiber-optic infrastructure, have shown to be an efficient paradigm for advanced applications like quantum secure communication, information processing, spectroscopy, imaging, and sensing. This review examines recent advancements in fiber- and chip-based platforms for generating non-classical states and their applications as quantum state processors in the time domain. We discuss the generation of pulsed quantum frequency combs using microring resonators and intra-cavity mode-locked laser schemes, enabling co- and cross-polarized quantum photonic states. Additionally, the versatility of these resonator chips for entanglement generation is emphasized, including two- and multi-photon time-bin entangled schemes. We highlight the development of time-bin entanglement analyzers in fiber architectures, featuring ultrahigh stability and post-selection-free capabilities, which enable precise and efficient characterization of two- and higher-dimensional time-bin entanglement. We also review scalable on-chip schemes for quantum key distribution, demonstrating low quantum bit error rates and compatibility with higher-dimensional quantum communication protocols. Further, methods for enhancing temporal resolution in detection schemes, crucial for time-bin encoding, are presented, such as the time-stretch sampling technique using electro-optic modulation. These innovations, relying on readily available, telecom-based fiber-optic components, provide practical, scalable, and cost-effective solutions for advancing quantum photonic technologies. Looking forward, time-bin encoding is expected to play a pivotal role in the advancement of quantum repeaters, distributed quantum networks, and hybrid light-matter systems, advancing the realization of globally scalable quantum technologies.